Etnobotani Tumbuahn Obat Berbasis Kearifan Lokal Masyarakat Pesisir Pulau Raam Distrik Sorong Kepulauan - Muzna Ardin Abdul Gafur; Zulkarnain Sangadji; Niny Jeni Maipauw; Hidayani Hidayani; Mercedes Fatie (Jurnal Penelitian Pertanian Terapan, 2026)
Ethnobotany of medicinal plants is a form of interaction between local communities and their environment. Local wisdom in the use of medicinal plants is also shaped by the ecosystem of the local area, whether it is coastal areas, mountains, forests, deserts and so on. Raam Island is one of the islands in the Sorong Islands District of Sorong City.  The lack of support for health facilities is one of the reasons why the people of Raam Island use local plants for first aid if they are attacked by disease.  Research data or written information about ethnobotany and local wisdom of the people of Raam Island, Archipelago District have not yet been found, so this research is expected to provide scientific information to the community, government, related agencies and all parties who need it.  The method used in this research is exploratory descriptive with survey methods and semi-structural interview techniques. The selection of respondents at this interview stage was carried out using the snowball sampling method, namely a technique for selecting respondents based on key informant recommendations.  The results of the research found 41 types of plants used as medicine, 85% of the parts used were the leaves.  As a tourism development area, it is important to increase attention to local wisdom in the use of medicinal plants on Raam Island. Keywords: Ethnobotany, medicinal plants, Raam Island